2014
DOI: 10.1590/s0034-8910.2014048005227
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle factors, direct and indirect costs for a Brazilian airline company

Abstract: OBJECTIVETo analyze lifestyle risk factors related to direct healthcare costs and the indirect costs due to sick leave among workers of an airline company in Brazil.METHODSIn this longitudinal 12-month study of 2,201 employees of a Brazilian airline company, the costs of sick leave and healthcare were the primary outcomes of interest. Information on the independent variables, such as gender, age, educational level, type of work, stress, and lifestyle-related factors (body mass index, physical activity, and smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The total indirect costs observed were higher for current smokers than former smokers, as described in previous studies. 9 , 49 …”
Section: Discussionmentioning
confidence: 99%
“…The total indirect costs observed were higher for current smokers than former smokers, as described in previous studies. 9 , 49 …”
Section: Discussionmentioning
confidence: 99%
“…These costs are expected to increase from $5.8 billion in 2010 to $10.1 billion by 2050 [ 31 ]. Furthermore, studies have established higher medication costs among patients with obesity [ 32 ], while a recent study of 2201 employees of a Brazilian airline found that obesity was associated with higher direct healthcare costs, with each BMI point increasing annual costs by $17 US dollars [ 33 ].…”
Section: Introductionmentioning
confidence: 99%